DIFFERENCES AND SIMILARITIES AMONG RURAL TOURISM IN SLOVENIA AND SERBIA – PERCEPTIONS OF THE LOCAL TOURISM WORKERS - Vujko, Aleksandra; Petrović, Marko D.; Dragosavac, Miloš; Gajić, Tamara (Economics of Agriculture, 2018)
This paper deals with the development of rural areas in Slovenia and Serbia and gives some differences/similarities among these two countries based on perception of 492 tourism workers. The article making a series of proposals to guide the future research agenda. The main aim of the paper is to point out the benefts of rural tourism development and its similarities and differences in Slovenia and Serbia. The data for this study were collected using Dwyer and Kims (2003) Integrated Model of Destination Competitiveness to observe Slovenias and Serbias rural tourism differences/similarities. Determinants were assessed using a survey evaluating 24 indicators (demand and supporting factors), based upon a Likert Scale.